A Review of Women with Epithelial Ovarian Carcinoma in a Middle-Income setting: Groote Schuur Hospital, Cape Town, South Africa: Demographics, Treatment and Outcomes of Patients between 2005 and 2015 - Loggenberg, Francisca (Department of Obstetrics and Gynaecology, 2025)
Background: In 2020 there were 313 959 new cases of Ovarian carcinoma worldwide.1 It is one of the most challenging female gynaecological cancers to manage with a poor prognosis for latestage disease and high recurrence rates. Ovarian Carcinoma ranks 8th amongst new cancer cases in women and accounts for 4.7% of reported cancer deaths.1 Women often present late with advanced disease of which the prognosis remains poor. The 5-year survival rate of stage 3 disease being 52-59% and only 17% for stage 4B disease.2 Overall the 5-year survival rate of many malignancies have improved over the past 30 years due to advances in screening, diagnosis and treatment, but despite these advances the survival rate of ovarian carcinoma has shown only a modest improvement.3 Methods: The study is a retrospective descriptive study of patients with epithelial ovarian carcinoma treated at Groote Schuur Hospital in Cape Town between 2005 and 2015. The study included all patients with epithelial ovarian carcinoma registered with and treated at our combined multidisciplinary clinic. There were 168 patients included in this study. Data was collected from patient folders and an existing cancer database(R016/2013). Data collection sheets were used and the data was entered into a secure database for analysis Results: The study population included 168 patients. The mean age was 59.4 years (standard deviation 11.6). High grade serous ovarian carcinoma was the most prominent histology accounting for 64.3% of cases. Endometroid and Mucinous histology was reported in 12.5% and 11.9% of cases respectively. Only 33.9% of patients presented with early-stage disease. Patients with advanced stage disease accounted for 66.1% of our study population. Of the 163 patients who underwent primary cytoreductive surgery, 72 (44.2%) patients were completely debulked with no residual disease, 18 (11%) were optimally debulked to less than 1cm residual disease and 72 (44.2%) still had gross residual disease. A complete response was achieved in 62.5% of our patients, 60 (57.1%) of these patients had recurrent disease with a median time to recurrence of 11.5 months. The median overall survival was 27.2 months with 5-year overall survival of 21%. The 5-year disease specific survival was 27%. Conclusion: Ovarian carcinoma remains one of the most challenging gynaecological malignancies to manage even in high resource settings. Rates of complete cytoreductive surgery were lower at our unit than reported in high income settings. Recurrence rates were high with shorter time to recurrence. The median survival of our patients was also much shorter than reported in literature. This may reflect the limitations in limited resource setting when managing patients with epithelial ovarian carcinoma.